Development of new towns in Poland. A case study of local labor markets - Cudo, Mateusz (Bulletin of Geography. Socio-economic Series, 2022)
The article attempts to assess the effect that obtaining urban status has on changes in the local labor markets of new towns. The analysis concerned those towns that were granted urban status for the first time between 1990 (the beginning of the transition to a market economy) and 2020. The analysis and research results did not show any significant correlation between the obtaining of urban status and improving labor market conditions. Despite the increase in entrepreneurship and the greater mobility of incoming employees, the localities did not become more attractive locations for medium-sized and large enterprises. Work-related population flows did not undergo major transformations and the range of influence of local labor markets was still mainly limited to the new towns’ own gminas, which together with the directly neighboring gminas formed functional urban areas that nonetheless rarely exceeded the boundaries of the poviat.